Evaluasi Efektivitas Efektif Mikroorganisme (EM) Berbasis Buah-Buahan Dan Sayur-Sayuran Dalam Menurunkan Parameter Pencemar Limbah Cair Tahu - Jonathan, Kenny; Goeltom, Mangihot Tua (Jayapangus Press, 2025)
Tofu wastewater consists of proteins, carbohydrates, fats, H2S, CO2 , CH4 and NH3 which endanger the life of aquatic biota. Tofu liquid waste has high BOD, COD, and ammonia and acidic pH exceeding standards. The high content of BOD and COD causes organisms to die due to lack of oxygen. Tofu waste processing can be done by adding microorganisms to degrade organic matter so that standards can be met. Microorganisms that are able to degrade tofu liquid waste belong to lactic acid bacteria and are found in fruits and vegetables. Microorganisms created inmixed cultures containing various kinds of microorganisms are called effective microorganisms (EM). The purpose of this experiment is to analyze the effectiveness of EM made from fruits and vegetables in processing tofu wastewater at various volumes through the parameters of BOD, COD, pH, ammonia, and pH. EM is made by mixing fruits and vegetables with sugar and coconut water which are fermented for 8 days. EM was mixed with waste at volume of 10 ml, 15 ml, 20 ml, 25 ml and incubated for 5 days. Parameters such as BOD, COD, ammonia, and pH were measured before and after incubation for 5 days. The number of coliform was also counted before and after incubation with TVC method. The findings demonstrate that adding EM at a volume of 25 ml produces the greatest outcomes since it lower the percentage of COD and ammonia reduction at the highest level while keeping the percentage of DO reduction at the lowest level.